MODELLING DYNAMIC STRESS CHANGES CAUSED BY AN EXTENDED RUPTURE IN AN ELASTIC STRATIFIED HALF-SPACE - Antonioli A.; Belardinelli M.E.; Cocco M. (My University, 2004)
We model the time histories of coseismic stress changes produced by an earthquake rupture on an extended fault in a layered elastic half-space. We compute the stress perturbations caused by earthquakes using the discrete wavenumber and the reflectivity methods. We investigate the influence on the computed Coulomb stress changes of the adopted crustal velocity model, the rupture history and slip duration as well as the poro-elastic model assumed to calculate the pore-pressure changes. The comparison between the spatio-temporal evolution of the induced stress field, calculated for different crustal models and rupture histories, allows us to assess the depth and frequency dependence of the induced stress perturbation and the relative weight of dynamic and static stress changes. Our results show that the rise time and the rupture directivity are more important for characterizing the simulated stress time histories than the details of the rupture history. The adopted poro-elastic model affects the static stress changes more than the transient stress perturbations. The results of this study should be taken into account to model fault interaction through elastic stress transfer.
Keywords: COULOMB STRESS; DYNAMIC STRESS; EARTHQUAKE RUPTURE; FAULT INTERACTION